2010
DOI: 10.1007/s11064-010-0307-z
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Stress Responses, Mitostress and Carnitine Insufficiencies as Critical Determinants in Aging and Neurodegenerative Disorders: Role of Hormesis and Vitagenes

Abstract: The widely accepted oxidative stress theory of aging postulates that aging results from accumulation of oxidative damage. A prediction of this theory is that, among species, differential rates of aging may be apparent on the basis of intrinsic differences in oxidative damage accrual. Although widely accepted, there is a growing number of exceptions to this theory, most contingently related to genetic model organism investigations. Proteins are one of the prime targets for oxidative damage and cysteine residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 219 publications
(441 reference statements)
0
63
1
1
Order By: Relevance
“…HO is present in various tissues with the highest activity in the brain, liver, spleen, and testes. There are three isoforms of heme oxygenase, HO-1 or inducible isoform [13,16,22], HO-2 or constitutive isoform [49], and the recently discovered HO-3, cloned only in rat to date [50]. Elevation of HO-1 expression and activity in MS is probably due to elevated oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HO is present in various tissues with the highest activity in the brain, liver, spleen, and testes. There are three isoforms of heme oxygenase, HO-1 or inducible isoform [13,16,22], HO-2 or constitutive isoform [49], and the recently discovered HO-3, cloned only in rat to date [50]. Elevation of HO-1 expression and activity in MS is probably due to elevated oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the sirtuin family have since been found to function as deacetylases for numerous protein targets involved in many cellular pathways, including cellular stress responses, apoptosis, and axonal degeneration. The activity of sirtuins can be regulated by other compounds that can serve as activators (e.g., plant polyphenols) that increase enzyme activity by lowering the Km of its substrates or that can serve as inhibitors (e.g., sirtinol) [15,16]. Neuroprotection mediated by SIRT1 activation has been demonstrated in axotomized dorsal root ganglion neurons and in neurons containing the Huntingtin gene mutation responsible for neurodegeneration in Huntington disease.…”
Section: Introductionmentioning
confidence: 99%
“…As aging reduces mental, physical or social activities in human beings, anti-aging has become a major public issue (Bao et al 2014). Accumulated evidence suggests that oxidative stress is an essential source for the process of biological aging, and reactive oxygen species (ROS) and reactive nitrogen species (RNS) play an important role by oxidizing DNA, lipid and protein macromolecules (Calabrese et al 2010;Obrenovich et al 2011;Fransen et al 2013). There is a general reduction in different physiologic functions which lead to agerelated diseases during aging in most organs.…”
Section: Introductionmentioning
confidence: 99%
“…Carnitine is an essential substance for the β-oxidation of fatty acids in mitochondria and is recognized as an antiaging nutrient (12,18). Several reports have shown that it Figure 2.…”
Section: Discussionmentioning
confidence: 99%